Climate change and the deteriorating archaeological and environmental archives of the Arctic. (27th June 2018) - Hollesen, Jørgen; Callanan, Martin; Dawson, Tom; Fenger-Nielsen, Rasmus; Friesen, T. Max; Jensen, Anne M.; Markham, Adam; Martens, Vibeke V.; Pitulko, Vladimir V.; Rockman, Marcy
Abstract: Abstract : The cold, wet climate of the Arctic has led to the extraordinary preservation of archaeological sites and materials that offer important contributions to the understanding of our common cultural and ecological history. This potential, however, is quickly disappearing due to climate-related variables, including the intensification of permafrost thaw and coastal erosion, which are damaging and destroying a wide range of cultural and environmental archives around the Arctic. In providing an overview of the most important effects of climate change in this region and on archaeological sites, the authors propose the next generation of research and response strategies, and suggest how to capitalise on existing successful connections among research communities and between researchers and the public.